2016
DOI: 10.1016/j.jpeds.2016.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Financial and Social Hardships in Families of Children with Medical Complexity

Abstract: Objective To describe hardships experienced by families of children with medical complexity (CMC) and compare them with those experienced by families of children with asthma. Study design We assessed hardships in a cohort of 167 families of CMC. Surveys assessed socio-demographics and hardships (e.g., financial: inability to pay bills; social: limited help from family/friends). CMC cohort hardships were compared with those of an established cohort of children hospitalized with asthma using multivariable logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 43 publications
1
96
0
Order By: Relevance
“…Optimizing family functioning must include unsilencing family narratives and amplifying parent experiences as story‐worthy. Barnert et al and Thomson et al stated the health of the child is intertwined with the health of the family and cannot be measured outside of the sphere of family health—the family is the patient. Our findings support acknowledging the family as a central unit of care; assisting parents with navigating and coordinating the broader social and medical systems; supporting disease and family transitions; and linking providers across institutions, community sites, and sectors …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimizing family functioning must include unsilencing family narratives and amplifying parent experiences as story‐worthy. Barnert et al and Thomson et al stated the health of the child is intertwined with the health of the family and cannot be measured outside of the sphere of family health—the family is the patient. Our findings support acknowledging the family as a central unit of care; assisting parents with navigating and coordinating the broader social and medical systems; supporting disease and family transitions; and linking providers across institutions, community sites, and sectors …”
Section: Discussionmentioning
confidence: 99%
“…Narratives from parents with children with disabilities have remained at the edge of larger medical and social systems, potentially contributing to parental needs being taken for granted and remaining unaddressed . Parents must become expert care providers addressing pervasive health and social needs, navigating fragmented discoordinated care within health‐care and government support systems, while carrying a heavy burden of care . Within the finite studies of parent experiences in caring for children with medical complexity, parents describe carrying significant emotional and social responsibility when caring for their children because of overwhelming circumstances and struggles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,108,109 Another significant factor that affected the use of CBPPC was financial support for families. The financial burden of caring for a child with LLI/LTI is signifi-cant: a study by Thomson et al (2016) 110 of children with medical complexity (not necessarily at the end of life) found that over 68% of families reported experiencing financial hardships (e.g., inability to pay bills). This financial burden is magnified at the end of life, particularly for children and families living in poverty and with other socioeconomic hardships.…”
Section: Discussionmentioning
confidence: 99%
“…Most research on CMC assisted by medical devices has explored caregiver experiences, 8,[12][13][14] overall use, 9,11 or single devices such as tracheostomy [15][16][17][18][19] or home oxygen therapy. 20,21 Reliable and valid indicators of device complication encounters are underdeveloped.…”
mentioning
confidence: 99%